Sintesis dan Karakterisasi Hidroksiapatit Dari Tulang Ikan Tuna (Thunnus Albacores) Dengan Xrf, Ftir, Dan Xrd - St Chadijah; Hardiyanti Hardiyanti; Sappewali Sappewali (Al-Kimia, 2018)
Hydroxyapatite (Hap) were inorganic compounds with constituent of bones and teeth has the molecular formula Ca5(PO4)3OH. Synthesis of hydroxyapatite can be done with  hydrothermal method  with calcium precursors tuna fish bone calcination process to obtain calcium compounds in the form   of calcium oxide. Calsium wich has been obtained added  phosphate precursor NH4H2PO4 0.547 M. On research conducted long stirring time variation and its effect on rendement and the resulting crystallites products. As for the variation of the long time of stirring used are 1, 2, 3, 4 and 5 hours. The optimum time of formation of hydroxyapatite obtained within 3 hours stirring from which content was 96.4156%. The material was analyzed by FTIR,XRF and XRD. Results showed their characterization by FTIR indicated the presence of OH groups,PO4  and CO3.  Based on the resulting diffraction of  XRF and XRD analysis, crystallite size obtained each of 41,9753  within 2 hours of stirring structure was hexagonal.